A new perspective on delivery of red-near-infrared light therapy for disorders of the brain - Hart, N.; Fitzgerald, Melinda (2016)
Red-near-infrared light has been used for a range of therapeutic purposes. However, clinical trials of near-infrared laser light for treatment of stroke were abandoned after failing interim futility analyses. Lack of efficacy has been attributed to sub-optimal treatment parameters and low penetrance of light to affected brain regions. Here, we assess penetrance of wavelengths from 450-880 nm in human post-mortem samples, and demonstrate that human skin, skull bone and brain transmits therapeutically relevant quantities of light from external sources at wavelengths above 600 nm. Transmission through post-mortem skull bone was dependent upon thickness, and ranged from 5-12% at peak wavelengths of 700-850 nm. Transmission through brain tissue ranged from 1-7%, following an approximately linear relationship between absorbance and tissue thickness. Importantly, natural sunlight encompasses the wavelengths used in red-near-infrared light therapy. Calculations of the average irradiance of light delivered by sunlight demonstrate that sunlight can provide doses of light equivalent to - and in some cases greater than - those used in therapeutic trials. Natural sunlight could, therefore, be used as a source of therapeutic red-near-infrared light, but equally its contribution must be considered when assessing and controlling therapeutic dose in patients. For targets deep within the brain, it is unlikely that sufficient doses of light can be delivered trans-cranially; therapeutic light must be supplied via optical fibers or implanted light sources.